Normothermic machine perfusion of donor livers without the need for human blood products - Matton, Alix P. M. (Liver Transpl, 2018)
Normothermic machine perfusion (NMP) enables viability assessment of donor livers prior to transplantation. NMP is frequently performed by using human blood products including red blood cells (RBCs) and fresh frozen plasma (FFP). Our aim was to examine the efficacy of a novel machine perfusion solution based on polymerized bovine hemoglobin‐based oxygen carrier (HBOC)‐201. Twenty‐four livers declined for transplantation were transported by using static cold storage. Upon arrival, livers underwent NMP for 6 hours using pressure‐controlled portal and arterial perfusion. A total of 12 livers were perfused using a solution based on RBCs and FFPs (historical cohort), 6 livers with HBOC‐201 and FFPs, and another 6 livers with HBOC‐201 and gelofusine, a gelatin‐based colloid solution. Compared with RBC + FFP perfused livers, livers perfused with HBOC‐201 had significantly higher hepatic adenosine triphosphate content, cumulative bile production, and portal and arterial flows. Biliary secretion of bicarbonate, bilirubin, bile salts, and phospholipids was similar in all 3 groups. The alanine aminotransferase concentration in perfusate was lower in the HBOC‐201–perfused groups. In conclusion, NMP of human donor livers can be performed effectively using HBOC‐201 and gelofusine, eliminating the need for human blood products. Perfusing livers with HBOC‐201 is at least similar to perfusion with RBCs and FFP. Some of the biomarkers of liver function and injury even suggest a possible superiority of an HBOC‐201–based perfusion solution and opens a perspective for further optimization of machine perfusion techniques. Liver Transplantation 24 528–538 2018 AASLD.